2017
DOI: 10.1016/j.ijvsm.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological risk factors of knowledge and preventive practice regarding avian influenza among poultry farmers and live bird traders in Ikorodu, Lagos State, Nigeria

Abstract: Avian Influenza (AI) is an infectious disease of birds caused by type A influenza virus. The disease has a pandemic risk leading to death or depopulation of millions of birds. This study determined the risk factors that predict adequate knowledge and good preventive practice measures towards AI, among poultry farmers and live bird traders in Ikorodu, Lagos State, South-western Nigeria.A descriptive cross sectional survey was conducted with questionnaire on socio- demographics, knowledge of definition, and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…By targeting all Eimeria species from a live bid market instead of a single poultry farm, our parasite detection rates should be higher [37] and our anticoccidial profile should be more representative of what is happening in the average chicken population in the field [35]. This is particularly so because live birds for sale at the market are often sourced from multiple farms [38], making such places important pathogen accumulation and distribution points [39].…”
Section: Discussionmentioning
confidence: 99%
“…By targeting all Eimeria species from a live bid market instead of a single poultry farm, our parasite detection rates should be higher [37] and our anticoccidial profile should be more representative of what is happening in the average chicken population in the field [35]. This is particularly so because live birds for sale at the market are often sourced from multiple farms [38], making such places important pathogen accumulation and distribution points [39].…”
Section: Discussionmentioning
confidence: 99%
“…The third category attempted to assign the responsibility elsewhere, either to buyers by making them aware of the animal's health condition or to the authorities who are responsible for issuing the pre-transportation veterinary certificate. In previous research among traders, lack of knowledge is a commonly stated reason for risky behaviours such as trading sick animals [30][31][32]34]. The traders in the current study trade diseased small ruminants for a span of different reasons and would therefore be likely to need different forms of intervention strategies to stop this risky behaviour.…”
Section: Discussionmentioning
confidence: 96%
“…To date, only a limited number of studies have been performed with the purpose of understanding the knowledge, attitudes and practices of traders related to animal health and disease. The majority of these are in the form of quantitative questionnaire studies and cover poultry trade and avian influenza (AI) [30][31][32] or pig trade and African or classical swine fever (ASF and CSF) [33,34]. Many of these studies focus on determining factual knowledge levels.…”
Section: Previous Research On Trader Perceptions and Practices Relatementioning
confidence: 99%
“…Given the observed variable epidemiological knowledge about, and inadequate preventive practices against HPAI H5N1 among age groups, gender and education in this study, training courses for peer groups is recommended such that educated traders can share their knowledge with others. Formal education is a very important factor that can promote traders' knowledge about HPAI and practices of biosecurity measures, as previously reported (Kuo et al, 2011, Elelu, 2017. Furthermore, delivery of messages via intermediaries such as traders' union leaders is suggested as it can be more effective than mass media or government communication programs.…”
mentioning
confidence: 90%
“…Their belief that HPAI is lethal only in birds further predisposes them to risk of likely human infection with the virus. Previous studies have reported low level of preventive practices against AI at LBMs and attributed it to low perceived threat by the workers (Manabe et al, 2011;Elelu, 2017). Hence public health campaign strategies that will involve education on zoonotic related risks to people involved in poultry business is advocated.…”
mentioning
confidence: 99%